Development of random mating population for genetic enhancement of yield traits in Indian mustard (Brassica juncea) - SINGH, V V; CHAUHAN, J S; MEENA, M L; SINGH, B R (The Indian Journal of Agricultural Sciences, 2014)
A random mating population of Indian mustard [Brassica juncea (L.) Czern. & Coss.] utilizing 20 germplasm accessions/promising donors for component traits, was developed from 2007-08 to 2009-10. Single plant progenies (180) termed as ‘half sibs’ were developed from this population and evaluated during 2010-11 in augmented block design along with standard checks. Observations were recorded on siliquae/ plant, siliquae length, seeds/siliqua, seed yield/plant and 1000-seed weight. The estimates of heritability were observed to be high 59.16 to 97.94% for all the characters. High heritability coupled with high genetic advance and GCV were observed for siliquae/plant and seed yield/plant. Maximum number of half sib progenies showed significant superiority for 1000 seed weight (39.44%) followed by seed yield/plant (10.55%), siliquae length (5.5%), siliquae/plant (5%) and seeds/siliqua (1.66%). These progenies may be utilized for initiation of second cycle of selection/development of trait specific gene pools.